2017
DOI: 10.1200/jgo.2015.002659
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Treating Childhood Medulloblastoma in a Country With Limited Resources: 20 Years of Experience at a Single Tertiary Center in Malaysia

Abstract: PurposePediatric medulloblastoma (MB) treatment has evolved over the past few decades; however, treating children in countries with limited resources remains challenging. Until now, the literature regarding childhood MB in Malaysia has been nonexistent. Our objectives were to review the demographics and outcome of pediatric MB treated at the University Malaya Medical Center between January 1994 and December 2013 and describe the challenges encountered.MethodsFifty-one patients with childhood MB were seen at Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…30 The incorrect risk stratification and the scarcity of standardized treatment protocols contribute to the different survival rates observed. 31 Of note, a study of pediatric brain tumors in India showed that over 25% of patients abandoned neuro-oncological treatments due to late diagnosis, complex multidisciplinary treatments, and lack of consistency in the management between different oncology centers. 32 Within this context, telemedicine might facilitate communication between advanced oncological centers and local primary care facilities, as demonstrated by successful initiatives in children with cancer and other catastrophic diseases conducted in low-middle income countries.…”
Section: Strokementioning
confidence: 99%
“…30 The incorrect risk stratification and the scarcity of standardized treatment protocols contribute to the different survival rates observed. 31 Of note, a study of pediatric brain tumors in India showed that over 25% of patients abandoned neuro-oncological treatments due to late diagnosis, complex multidisciplinary treatments, and lack of consistency in the management between different oncology centers. 32 Within this context, telemedicine might facilitate communication between advanced oncological centers and local primary care facilities, as demonstrated by successful initiatives in children with cancer and other catastrophic diseases conducted in low-middle income countries.…”
Section: Strokementioning
confidence: 99%
“…High income countries report incidence rates of 20%‐25%, whereas low to middle income countries report 6.1%‐49.4% . Diagnostic and treatment protocols vary across the world due to—among other things—financial and logistic factors . Ultimately, these inconsistencies can result in a disparity of survival rates and HRQL .…”
Section: Discussionmentioning
confidence: 99%
“…Survival rates for medulloblastoma have increased significantly due to improved treatment methods, with five year survival rates that range from 70% to 85% . However, there is a disparity in survival rates in low to middle income countries—ranging from 33% to 73% . Social, cognitive, and neurological long‐term late effects have the potential to compromise the ongoing quality of life of survivors worldwide .…”
Section: Introductionmentioning
confidence: 99%
“…This group received definitive surgery followed by chemotherapy, which played an essential role in the treatment of this infantile group because it allowed one to delay the use of radiation for these patients, who received neoadjuvant chemotherapy and reduced the harm to the developing nervous system in this age group. 17 The most common toxicity in our studied patients was blood toxicity in the form of myelosuppression. Forty-nine patients developed grades 3 and 4 blood toxicity during treatment.…”
Section: Survival Functionmentioning
confidence: 91%